Hvem er ærens konge, der? - Damgaard, Andreas Riis (Dansk Teologisk Tidsskrift, 2017)
Sigmund Mowinckel created a highly influential interpretation of the Psalter. In this interpretation, Ps 24 played a particularly important role due to its antiphonic style. The antiphonic style of the psalm is widely represented in the reception history of the psalm – especially in classical music. For example, Handel's chorus piece Lift up ye Heads in his oratorio Messiah is structured in an antiphonic manner. Mowinckel’s exegesis and the music composed by Handel have similar structures in their representations of Ps 24 – in spite of the different aims of their interpretations. However, both interpretations are concerned with God’s victory over death. It is fruitful to note the similarities of the two interpretations, because they suggest either a Christian hermeneutical background to Mowinckel's enthronement festival or an antiphonic style in the text itself.